Systematic Literature Review: Pengembangan LKPD Berbasis Problem Based Learning (PBL) pada Materi Sistem Pencernaan Manusia - Yuliastrin, Adisti; Yovita, Yovita; Pratiwi, Tiara Alvionita; Yusrianto, Edi; Vebrianto, Rian (Journal of Natural Sciences, 2025)
The transformation of education from the Industrial Revolution 4.0 to Society 5.0 demands the development of 21st-century skills. In science learning, the human digestive system is considered complex, requiring adaptive instructional media. A systematic literature review using the PRISMA method was conducted on 20 articles from Scopus, Google Scholar, and Connected Papers (2020–2024). Inclusion criteria focused on the development of Problem-Based Learning (PBL)-based student worksheets (LKPD) and content related to the digestive system. About 85% of the articles targeted the junior high school level. All studies reported that PBL-based LKPD improved conceptual understanding, critical thinking, collaboration skills, and scientific literacy. Approximately 60% incorporated interactive technology-based media. PBL-based LKPD is proven to be feasible and effective in supporting the Merdeka Curriculum and fostering contextual and meaningful learning in the digital era.